Longitudinal strain combined with delayed-enhancement magnetic resonance improves risk stratification in patients with dilated cardiomyopathy. Issue 9 (31st October 2016) - Chimura, Misato; Onishi, Tetsuari; Tsukishiro, Yasue; Sawada, Takahiro; Kiuchi, Kunihiko; Shimane, Akira; Okajima, Katsunori; Yamada, Shinichiro; Taniguchi, Yasuyo; Yasaka, Yoshinori; Kawai, Hiroya
Abstract : Objective: Late gadolinium enhancement (LGE) on cardiac magnetic resonance (CMR) imaging has been reported to be associated with unfavourable outcomes; however, few studies have addressed the prognostic value of left ventricular (LV) deformation parameter indicated by global longitudinal strain (GLS) in two-dimensional speckle-tracking (2DST) echocardiography in patients with non-ischaemic dilated cardiomyopathy (DCM). This study aims to investigate whether the combination of GLS and LGE is useful in stratifying the risk in patients with DCM. Methods: We studied 179 consecutive symptomatic patients with DCM (age, 61±15 years; 121 males; left ventricular ejection fraction (LVEF) 33%±9%; New York Heart Association (NYHA) class II: n=71, III: n=107, IV: n=1) who underwent CMR and echocardiography with conventional assessment and 2DST analysis. Results: There were 40 rehospitalisations for heart failure, including 7 cardiac deaths and 2 implantations of LV assist device during follow-up (3.8±2.5 years). Univariable Cox proportional hazard regression analysis showed that NYHA class, blood pressure, B-type natriuretic peptide, LV end-diastolic and end-systolic volumes, LVEF, left atrium volume, GLS and LGE were significantly associated with long-term outcome. Multivariable analysis revealed that GLS and LGE were independently associated with long-term outcome (p<0.05, both). In additional analyses, we found independent associations between GLS and LV reverse remodelling after the optimal medical therapy, and between LGE and life-threatening arrhythmias (p<0.05, both). Conclusion: Combining GLS and LGE could be useful for risk stratification and prognostic assessment in patients with DCM.